Erfassung und Analyse von Wegmerkmalen und Laufbelastungen im Hallenhandball und ihre Auswirkungen auf die Trainingspraxis, mit besonderer Berücksichtigung der Computerunterstützung - Leitner, R. (1993)
The thesis deals with a newly developed analysis of games. By means of a videoanalyzer co-ordinates are being measured out from a screen picture which afterwords are being transfigured into real space co-ordinates. From these findings you can dedect the length of tracks that have been run, the speed and the necessary energy required for these activities. A survey will be given about the distribution of running stress during a game. Moreover the space of action being required during a game can be figured out. Such an analysis of position enables the finding of specific qualities from then personal players' dates. Motorical tests that have been carried through previously provide of basis for the assessment of running power. For a basic interpretation of the results they are transformed into standard rates and demonstrated graphically. The running distance covered during a game is about 5000 m. Considering a 60 minutes period of game, this amounts to a rather great regenerative load. The time of load is interpersed with short, highly energetic peak loads lasting as an average of 2.5 seconds at a load density of about 70 seconds. The progress of general endurance efficiency and the results concerning structure of burden ought to lead to a revision of the hither to used training doctrines. For broader experimental series the development of better automatic data registration instruments should be envisaged.